PREVALENCE OF THYROID DYSFUNCTION IN TYPE 2 DIABETIC PATIENTS - PROF.DR.V.PADMA; PROF.DR.N.N.ANAND (International Journal of Pharma and Bio Sciences, 2015)
Abnormal thyroid hormone levels occur in diabetes mellitus AIM: To find out the prevalence of thyroid dysfunction in type 2 diabetic patients. MATERIALS AND 100 diabetic and 100 nondiabetic age and sex matched subjects were selected and thyroid function test was performed. Out of 100 diabetics subjects studied, 18% had low plasma thyroid hormone levels ,16% had raised plasma thyroid hormone levels and 66 % were euthyroid . This study has shown a high incidence of abnormal thyroid hormone levels among the diabetics(34%). DISCUSSION: Iodothyronines are insulin antagonist with high levels being diabetogenic while the absence of the hormone inhibits the development of diabetes. A higher frequency of retinopathy and nephropathy was observed in diabetic patients with subclinical hypothyroidism. Routine assessment of thyroid hormone levels is necessary in diabetics. The ability to diagnose and treat unsuspected hypothyroidism in these patients may greatly enhance the quality of life.